(untitled) (Лучшие интеллектуальные исследования, 2024)
In higher education, laboratory work is frequently used to illustrate mechanical processes in technical topics. It cannot be assumed, nonetheless, that these activities are carried out correctly everywhere. The utilization of virtual laboratory exercises is a useful substitute to improve this weakness. Furthermore, logical inferences about the processes are made possible by immediately transferring measured mechanical and physical parameters to computer memory. The global market offers a variety of reasonably priced chips made for monitoring mechanical and physical properties. By taking advantage of these features, measured parameter values can be sent straight to computer memory, doing away with the requirement for pricey measurement devices. The process of recording and creating bootloader programs (applications) is the main topic of this article, which also shows how random numbers produced by the computer (randomizer) are used to replace data transmitted from chips.